THE IMPACT OF COVID-19 ON STOCK MARKET RETURNS - Jessica, Jessica; Yanti, Yanti (International Journal of Application on Economics and Business, 2023)
This study is done to analyze the effect of COVID-19 on stock returns in manufacturing companies listed on the Indonesian Stock Exchange (IDX) from March 2, 2020 to December 31, 2020. Sample was selected using purposive sampling method and the valid data was 167 companies. This study uses a fixed effect model and multiple linear regression analysis and analyzed utilizing EViews 12. The results in this study indicate that the daily growth in total confirmed COVID-19 cases, daily growth in total COVID-19 deaths and Large-Scale Social Restrictions (PSBB) has a negative significant effect on stock returns, while daily growth in total recovered COVID-19 cases has an insignificant effect on stock returns.